2022
DOI: 10.1002/crat.202100285
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the Photocatalytic Degradation Efficiency of Solution Combustion Derived ZnO Photocatalyst through Palladium Doping

Abstract: In this work, palladium-doped zinc oxide nanoparticle photocatalysts with various amounts of palladium are prepared through a solution combustion method. Their crystal structure, optical, morphological, and thermal properties are examined by X-ray diffractometry (XRD), UV-vis Diffuse Reflectance Spectroscopy (DRS), scanning electron microscopy (SEM), and thermogravimetric analysis, respectively. The XRD results demonstrate that palladium doping does not induce any secondary phases related to metallic palladium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Previous studies on the synthesis of cobalt sulfide and various composites have demonstrated their effectiveness as photocatalysts for the degradation of dyes like methylene blue [30][31][32][33][34][35]. Due to their optimal combination and high reactivity, palladium is widely used as an intermediate metal in homogeneous and heterogeneous catalytic reactions, being one of the most consumed metals [36][37][38][39]. Generally, heterogeneous catalytic processes are preferred over homogeneous processes due to higher efficiency and easier reuse of catalyst materials.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the synthesis of cobalt sulfide and various composites have demonstrated their effectiveness as photocatalysts for the degradation of dyes like methylene blue [30][31][32][33][34][35]. Due to their optimal combination and high reactivity, palladium is widely used as an intermediate metal in homogeneous and heterogeneous catalytic reactions, being one of the most consumed metals [36][37][38][39]. Generally, heterogeneous catalytic processes are preferred over homogeneous processes due to higher efficiency and easier reuse of catalyst materials.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of crystals with specific morphology and size has become a hot topic since the properties of a composite material rely heavily on its micro-nano structures. [1][2][3] Zinc oxide (ZnO) stands out among these materials due to its variable morphologies and remarkable optical properties, finding applications in catalysts, [4] photoelectric devices, [5] solar cells, [6] cosmetic industry, [7] antimicrobial agents, [8] rubber, [9] and so forth. Up to date, ZnO with various morphologies, such as wires, [10] snowflakes, [11] cylinders, [12] tubes, [13] stars, [14] dendrite sheets, [15] plates, [16] dumbbells, [17] disks, [18] and so on, have been successfully prepared as a functional filling employed in many occasions.…”
Section: Introductionmentioning
confidence: 99%